2021
DOI: 10.1016/j.marenvres.2021.105441
|View full text |Cite
|
Sign up to set email alerts
|

Is starvation a cause of overmortality of the Mediterranean sardine?

Abstract: Animal mortality is difficult to observe in marine systems, preventing a mechanistic understanding of major drivers of fish population dynamics. In particular, starvation is known to be a major cause of mortality at larval stages, but adult mortality is often unknown. In this study, we used a laboratory food-deprivation experiment, on wild caught sardine Sardina pilchardus from the Gulf of Lions. This population is interesting because mean individual phenotype shifted around 2008, becoming dominated by small, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…In our study, despite a decrease in respiration after 60 days of food deprivation, the metabolic rate of food deprived fish at 20°C remained higher than that measured at 12°C in fed or food deprived fish. Moreover, as observed in Queiros et al, 2021, the respiration of sardines food deprived at 20°C actually increased after 50 days of food deprivation, which may indicate an entry into the critical fasting phase (Bar, 2014;Queiros et al, 2021). At a cellular level, the combination of food deprivation and warmth for 60 days elicited energy-saving mechanisms characterized by a decrease in mitochondrial maintenance costs (i.e.…”
Section: Interaction Between Temperature and Food Deprivationmentioning
confidence: 71%
See 1 more Smart Citation
“…In our study, despite a decrease in respiration after 60 days of food deprivation, the metabolic rate of food deprived fish at 20°C remained higher than that measured at 12°C in fed or food deprived fish. Moreover, as observed in Queiros et al, 2021, the respiration of sardines food deprived at 20°C actually increased after 50 days of food deprivation, which may indicate an entry into the critical fasting phase (Bar, 2014;Queiros et al, 2021). At a cellular level, the combination of food deprivation and warmth for 60 days elicited energy-saving mechanisms characterized by a decrease in mitochondrial maintenance costs (i.e.…”
Section: Interaction Between Temperature and Food Deprivationmentioning
confidence: 71%
“…In vivo group metabolism was measured as oxygen consumption by the sardines in their custom-designed holding tanks, using automated stop-flow respirometry (Steffensen, 1989) modified for open tanks (McKenzie et al, 2007;McKenzie et al, 2012), exactly as described in Queiros et al (2021). Briefly, this system alternated periods in a cycle comprising 30 min when the tanks were aerated and received a water supply versus 30 min when water supply and aeration were stopped, and the fish consumed the oxygen in the water.…”
Section: In Vivo Oxygen Consumptionmentioning
confidence: 99%
“…An increased mismatch between the spring peak of zooplankton biomass (mainly calanoids) and the growth phase of small pelagic fish [84][85][86] could certainly explain their body condition. In their experimental study, Queiros et al [87], showed that sardine can display adaptative phenotypic plasticity to food condition changes. Under lower food quantity and quality conditions, the smallest phenotypes experienced lower mortality by starvation than the larger ones during the critical post-reproductive period (i.e.…”
Section: Plos Onementioning
confidence: 99%